Adaptation and validation of the Protein Screener 55+ to identify low protein intake among community dwelling older adults in New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Nutrition and Dietetics at Massey University, Albany, New Zealand - Malcolm, Brittany Barbara (Massey University, 2020)
Background: Recent research suggests at least 1.0g dietary protein/kg/day is required to maintain muscle mass strength and functionality in older age (Campbell, Trappe et al. 2001, Beasley, LaCroix et al. 2010, Houston, Tooze et al. 2017). The Protein Screener 55+ is a screening tool, developed in the Netherlands, to identify community dwelling older adults at risk of low protein intake (≤1.0g/kg adjusted body weight/day). In New Zealand there is currently no rapid method to screen for low protein intake in older adults. Therefore, the aim of this research was to adapt and validate the Protein Screener 55+ to detect low protein intake (≤1.0g/kg adjusted BW/day) in community dwelling older adults in New Zealand. Methods: Protein intake was assessed among 367 community dwelling older adults aged 65 to 74 years using a 109-item food frequency questionnaire and a four-day food record. Univariate and multivariate logistic regression analysis was used to select food items which predicted protein intake ≤1.0g/kg adjusted body weight/day; based on amount (g/day) and frequency (over four weeks) from both the FFQ and the food record (to assess relative validity). A final restricted prediction model (screening tool) was developed and tested using a receiver operating characteristic (ROC) curve, to test the screening tool’s discriminatory capacity for protein intake ≤1.0g/kg adjusted body weight/day. For ease of use, recoded frequency variables (from gram amounts of protein) were used for each protein predictor variable in the final tool. Results: Participants were mostly female (63.9%), New Zealand European (94.3%) and of higher socioeconomic status (New Zealand Index of Multiple Deprivation score 1-4; 59.2%). Mean protein intake was 1.1± 0.4g per kg adjusted body weight per day and 152 (42%) had a protein intake ≤1.0g per kg of adjusted body weight per day. The final screening tool for predicting low protein intake based on frequency of intake included: beans; beef, mutton, lamb, pork; poultry; eggs; fish; milk and yoghurt. The area under the receiver operating characteristic curve was 0.835 (95% CI 0.794-0.876). Conclusion: The adapted Protein Screener 55+ is a valid tool for detection of low protein intake among this group of community dwelling older adults in New Zealand. Further validation is needed to ensure applicability to the wider older adult population.
Keywords: 321005 Public health nutrition